Analysis of morphological parameters of vertebrae in domestic geese and ducks - Wang, Jiajia; Zhang, Zheng; Zhou, Kailong; Jiang, Xinming; Huang, Dongyan; Qian, Zhihui; Ren, Lei; Ren, Luquan (Frontiers in Veterinary Science, 2025)
BackgroundBirds have evolved morphologically diverse neck structures in order to adapt to different foraging styles. Studying avian neck structure and function can not only help us understand their evolutionary processes and ecological roles, but also use them as a research model for modular structure, providing a valuable reference for exploring the morphological and kinematic properties of other organisms.ObjectiveBy analyzing the neck bone structure of Chinese geese and domestic ducks, referring to the characteristic parameters of the neck bone structure, it provides reference for the structural design of bionic bird neck machinery.MethodsThis study focuses on two representative avian species of the order Anseriformes—geese and ducks—as research subjects to analyze their cervical vertebral structural morphology and investigate characteristic parameters of their cervical skeletal system. This manuscript mainly includes the following contents: structural morphological dimensions of goose and duck vertebrae were manually measured, and characteristic curves were plotted, analysis of their skeletal structural features. Images of the surface structural morphology of goose and duck vertebrae were taken, processed and measured with Image J software. Through comparative analysis of the morphological characteristics of vertebral surface structures in geese and ducks, their patterns were summarized.ConclusionThe vertebral morphological characteristics of domestic geese and domestic ducks are very similar. With the increase of vertebral length (CL), the fluctuation range of vertebral width (ZW) gradually increases, and the fluctuation trend of vertebral width (ZW) of goose and duck neck is basically the same. The overall changes of the goose cervical CL values were smaller as compared to the duck cervical spine. Furthermore, although geese and ducks differ in cervical spine numbers, both showed functional zoning similar to other birds.